2019
DOI: 10.1016/j.immuni.2019.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Proliferating Transitory T Cells with an Effector-like Transcriptional Signature Emerge from PD-1+ Stem-like CD8+ T Cells during Chronic Infection

Abstract: T cell dysfunction is a characteristic feature of chronic viral infection and cancer. Recent studies in chronic lymphocytic choriomeningitis virus (LCMV) infection have defined a PD-1 + Tcf-1 + CD8 + T cell subset capable of self-renewal and differentiation into more terminally differentiated cells that downregulate Tcf-1 and express additional inhibitory molecules such as Tim3. Here, we demonstrated that expression of the glycoprotein CD101 divides this terminally differentiated population into two subsets. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

35
409
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 435 publications
(496 citation statements)
references
References 73 publications
35
409
0
Order By: Relevance
“…2d). Cells expressing CX3CR1 also highly expressed GZMB and PRF1 , consistent with previous reports that CX3CR1 marks a CD8 + T cell population with superior cytolytic function corresponding to a more differentiated effector phenotype that has been observed in models of chronic infection and other cancers 4143 . We did not observe a distinct cluster of TCF7 and SLAMF6 dual-expressing progenitor cells previously reported to mediate response to anti-PD-1 therapy in melanoma (Extended Data Fig.…”
Section: Cytotoxic Cell States and Dynamicssupporting
confidence: 91%
See 1 more Smart Citation
“…2d). Cells expressing CX3CR1 also highly expressed GZMB and PRF1 , consistent with previous reports that CX3CR1 marks a CD8 + T cell population with superior cytolytic function corresponding to a more differentiated effector phenotype that has been observed in models of chronic infection and other cancers 4143 . We did not observe a distinct cluster of TCF7 and SLAMF6 dual-expressing progenitor cells previously reported to mediate response to anti-PD-1 therapy in melanoma (Extended Data Fig.…”
Section: Cytotoxic Cell States and Dynamicssupporting
confidence: 91%
“…This population was uncommon in bone biopsies, which instead contained clonally expanded CD8 + T cells with high effector molecule, low exhaustion marker, and CX3CR1 expression. This cell state has previously been linked in model systems and other cancers to high cytolytic activity but poor proliferative potential and a requirement for CD4 help 4143 . Similar cells have been reported as being unresponsive to PD-L1 blockade, potentially explaining the poor performance of immune checkpoint inhibition in mCRPC bone metastases 1,49 .…”
Section: Discussionmentioning
confidence: 92%
“…In contrast to the antibody repertoires following LCMV infection, we observed minor differences in the TCR repertoires between acute and chronic cohorts, including the upregulation of the TRBV30 in both spleen/LN and lung repertoires in chronic infection ( Figure 6B) and virus-specific clones restricted to a particular infection cohort ( Figure 6A). Overall, the repertoire structure was strikingly similar between the two infection conditions, further suggesting that phenotypic diversity plays a larger role than CD8 T cell repertoire diversity in response to LCMV infection (Chen et al, 2019;Siddiqui et al, 2019;Hudson et al, 2019). Further experiments investigating the CD4 T cell landscape may provide more apparent differences between the two infection cohorts and Tcf1+ and Tcf1-populations, given both the role of T follicular helper cells in chronic infection and that previous studies performing CD4 depletion have demonstrated that the terminally differentiated Tcf1-population shrinks but not in the proliferation-competent CD8 T cells (Greczmiel et al, 2017;Kanev et al, 2019).…”
Section: Discussionmentioning
confidence: 93%
“…We observed the emergence of CX3CR1 + cells in the subacute phase even in the absence of TCF-1 + cells or CD4 T cell help. Recent studies have described a similar population and concluded that CX3CR1 + cells constitute a transitional population downstream of TCF-1 + exhausted cells using adoptive transfer (37). It is likely that TCF-1 + cells retain potential to give rise to CX3CR1 + cells as they generate CX3CR1 + cells and terminally differentiated cells upon adoptive transfer or PD-1 blockade.…”
Section: Discussionmentioning
confidence: 96%